Adherence to Fluid Restriction of Chronic Kidney Disease Patients Undergoing Hemodialysis - Aji, Oktavian Kuncoro; Yuwono, Podo; Nugroho, Fajar Agung (Prosiding University Research Colloquium, 2022)
Background: Fluid restriction on Chronic Kidney Disease who undergoing hemodialysis is an essential thing to do it. Over fluid status will cause edema, overweight, bronchitis, swollen eyelids, and breathlessness. That all are symptoms of Chronic Kidney Disease (CKD). Purpose: to know adherence to fluid restriction on chronic kidney disease patients undergoing hemodialysis Method: This research is a descriptive quantitative research using a case study approach, with a population of 176 hemodialysis patients, 122 samples used using purposive sampling technique of hemodialysis patients at Dr. Soedirman Hospital Kebumen. Data collection was carried out using a questionnaire instrument for Liquid Restriction Compliance Levels using univariate analysis Result: Of the individuals included in the study, 58.5% were aged 46–65 years age, 52.8% were male, 34.1% were primary school graduates, 57.7% were not working, 88.6% were married, 43.9% had taking 13-36 months of hemodialysis therapy, and 58.5% were in adherence to fluid restriction category. Conclusion: This study stated that the majority of the respondents were in adherence to fluid restriction. Recommendation: Further, health care services like hospitals can modify education strategies toward fluid restriction on hemodialysis patients.